Asymptotische Entwicklung der Verteilungsgesetze einiger Funktionen auf den geordneten Halbgruppen mit regulärer Normierung - Juškys, Z. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:З. Юшкис. Асимптотическое разложение законов распределения некоторых функций, определённых на упорядоченных полугруппах с регулярной нормировкойZ. Juškys. Kai kurių funkcijų, apibrėžtų sutvarkytuose pusgrupiuose su reguliariu normavimu, pasiskirstymo dėsnių asimptotinės formulės